The effect of the firm’s innovation modes DUI and STI on radical innovation and the moderating role of institutional factors in an emerging economy (2019)
Innovation modes literature explains how firms use and combine scientific and experience-based knowledge to adopt innovation outcomes. Moreover, the association between innovation modes and innovation outcomes differ due to institutional factors. Since innovation modes use and combine heterogeneous knowledge to produce innovation outcomes, institutions can strengthen or weaken knowledge use involve in the innovation process. This paper analyzes how institutional factors, such as ease of imitation, and difficult to access external financing, moderate the effect of the firm’s innovation modes on radical innovations. We use an innovation survey from an emerging economy and apply a multilevel technique. Our main results state that firms adopting a DUI or a DUI-STI mode have a positive association with radical innovation, and this effect is stronger for low levels of imitation, while STI mode is detrimental for adopting radical innovation, but high imitation contributes positively to radical innovation. On the other hand, access to external financing has a negative moderator effect in DUI and STI modes introducing radical innovation